2014
DOI: 10.3233/wor-131788
|View full text |Cite
|
Sign up to set email alerts
|

Employment outcomes among African Americans and Whites with mental illness

Abstract: BACKGROUND: People with mental illness often experience major difficulties in finding and maintaining sustainable employment. African Americans with mental illness have additional challenges to secure a job, as reflected in their significantly lower employment rates compared to Whites. OBJECTIVE: To examine the factors that contribute to racial disparities in employment outcomes for African-American and White Vocational Rehabilitation (VR) consumers with mental illness. METHODS: This study used VR data from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…For example, people who received the most daily support (24 hr a day) and mid-level support (6–12 hr) also had lower odds of having fair-wages than those who only received support as needed. This mirrors previous research findings about the relationship between severe impairments and poor employment outcomes (Lukyanova et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, people who received the most daily support (24 hr a day) and mid-level support (6–12 hr) also had lower odds of having fair-wages than those who only received support as needed. This mirrors previous research findings about the relationship between severe impairments and poor employment outcomes (Lukyanova et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…For example, people who received the most daily support (24 hr a day) and mid-level support (6-12 hr) also had lower odds of having fair-wages than those who only received support as needed. This mirrors previous research findings about the relationship between severe impairments and poor employment outcomes (Lukyanova et al, 2014). Our findings regarding individual-level factors that produce lower odds for fair-wages, especially those that relate to more support needs, may appear to be an obvious barrier to types of employment that result in fair-wages in the current US employment model.…”
Section: Discussionsupporting
confidence: 86%
“…Health disparities across subpopulations with PDs may be attributed to the differences in gender, which may be overlooked by researchers and healthcare providers. 68 This study contributes to a literature that suggests how SRH is contextualized among vulnerable populations, such as aging AAs with PDs. A unique advantage of the current study was to analyze the health profile of low-income community-dwelling AA adults with PDs, which have not been studied extensively in the literature.…”
Section: Resultsmentioning
confidence: 89%
“…However, in practice in the USA, outside the confines of such trials, ethnic minority patients are often offered different services and face challenges accessing vocational rehabilitation services (Olney 2002). Lukyanova et al (2014), for example, found that ethnic minority individuals with mental illness engaging in vocational rehabilitation have poorer employment outcomes than White individuals.…”
Section: Box 3 Rehabilitation and Recovery Definedmentioning
confidence: 99%